2007
DOI: 10.1182/blood-2006-08-034447
|View full text |Cite
|
Sign up to set email alerts
|

Biology of umbilical cord blood progenitors in bone marrow niches

Abstract: Within the bone marrow (BM), hematopoietic progenitor cells (HPCs) are localized in poorly oxygenated niches where they interact with the surrounding osteoblasts (OBs) through VLA4/VCAM-1 engagement, and are exposed to interleukin-6 (IL-6), stem cell factor (SCF), and chemokines such as CXCL12 (OB factors). Umbilical cord (UC) is more highly oxygenated that the BM microenvironment. When UC-HPCs are exposed to the 2% to 3% O 2 concentration found in the bone endosteum, their survival is significantly decreased.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 59 publications
1
43
0
Order By: Relevance
“…Recent data suggest that the hematopoietic stem cell niche may be less supportive of cord blood than adult hematopoietic stem cells. 20 The more stem cells infused, the greater the probability that an amount sufficient to promote engraftment would arrive at and survive occupation of the niche space.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that the hematopoietic stem cell niche may be less supportive of cord blood than adult hematopoietic stem cells. 20 The more stem cells infused, the greater the probability that an amount sufficient to promote engraftment would arrive at and survive occupation of the niche space.…”
Section: Discussionmentioning
confidence: 99%
“…The strongest evidence for niche-based regulation in mammalian tissue probably comes from studies of spermatogenesis. Similar studies in other self-renewing tissues have revealed a close interaction of stem cells and stromal cells that constitute the niche [5]. SSCs expand in the presence of feeder layer cells such as mouse embryonic fibroblast (MEF) cells, SIM mouse embryo-derived thioguanine and ouabain resistant STO cells and human embryonic cell-derived fibroblast-like cells (hEFs) [6].…”
Section: Introductionmentioning
confidence: 70%
“…Further studies involving CD96 and ITP physiology might provide insight of normal CD96 functions. Niche biology plays an important role in an overall fate of stem cell; bone marrow and cord blood are two different microenvironments based on their anatomy, availability of oxygen, cytokines and cell signaling (19). In recent years there are increased efforts in studying UCB progenitors in bone marrow environment due to their obvious ease of availability for therapeutic purpose (20).…”
Section: Resultsmentioning
confidence: 99%